The Use of QR Code-Based Arabic Ewan Textbooks in Learning Mahārah Kalām - Salamah, Ummu; Wibisono, Muassomah (STIQ Amuntai, 2024)
Learning Arabic for beginners Of course, you really need a guide book in learning a language. The book does not seem archaic and monotonous but a textbook that is creative, innovative and easy to understand for students. Al Maahira IIBS Malang, recently this institution launched the implementation of a very interesting textbook adopted from Ewan University, namely the book